On editorial interlocution: presence of the other in text workers’ activity - Muniz Júnior, José de Souza (2011)
This paper discusses, on a discursive perspective, the functioning of the otherness on editorial treatment of texts. We analyse two aspects: first, the enunciative places that establish themselves one by the other — author and reader; second, the discursive memories that delimit its execution, always inscribed in a specific field. We stand out the inseparability between the text and its production conditions, considering the relations among the several discourses that regulate this work, restricting its possibilities or enlarging them.